Performance Evaluation of Faffa Food Share Company through Computerized Maintenance Management System (CMMS) - Gadisa Alemayehu; Muralidhar Avvari; Bikila Alemu; Atkilt Mulu Gebrekidan (Journal of Engineering)
Since 1962 EC, the Faffa Food Share Company has been producing and supplying flour in Ethiopia both for relief and commercial markets. However, it is incompetent in the market due to a poor maintenance management system. So, the aim of this research is to overcome the poor maintenance management problems by using the CMMS application. The data collected from the company by survey studies, unstructured interviews, and stopwatches and from company records revealed that frequent failure machines, as well as a poor maintenance management system, cause production downtimes, resulting in a 29.19% decrease in production from the planned production. The collected data are analyzed by, tools such as time and motion study, SPSS software and CMMS effectively. The finding from the outcome of the bivariate correlation of CMMS elements and manufacturing performance dimension has an alpha α value of greater than 0.5, which indicates that the relationships between CMMS and manufacturing performance are positive. The findings from company records and stopwatch equipment and manpower (technicians) should be managed to activate machine servicing. Finally, the proposed smart maintenance management system tool, CMMS improves the availability of machines, reduces the frequency of equipment failure, reduces the breakdown time, decreases the cost of maintenance, and then improves the manufacturing performance by 5 percent.